2023
DOI: 10.1111/ans.18506
|View full text |Cite
|
Sign up to set email alerts
|

Advanced skills for general surgeons and carving out a niche: Endoscopic retrograde cholangiopancreatography in regional Australia

Abstract: Background The provision of high‐quality healthcare in rural Australian hospitals has necessitated general surgeons to take up the challenge and expand their expertise to advanced endoscopy techniques including endoscopic retrograde cholangiopancreatography (ERCP). This study examines the utility of ERCP in a regional setting especially in decreasing patient transfers and associated costs while achieving exceptional safety by measuring key indicators of safety and efficacy. Methods A single‐centre retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Management of choledocholithiasis in regional settings can often be challenging due to limited access to sub-specialist care, which may limit a health network's ability to provide quick access to specialized procedures. A recent review of 191 consecutive patients [18] who had an ERCP performed by a trained general surgeon in a regional center found that the procedure was completed well above published standards and was cost-effective when comparing overall management costs. Furthermore, despite perceived difficulties surrounding a CBDE, Hodgson et al [19] reported that a caseload of 70 CBDE over 10 years was sufficient in producing an 80% success rate, with only one procedure a year needed to maintain a safe procedure with a 50% success rate.…”
Section: Management Of Choledocholithiasis In a Regional Settingmentioning
confidence: 99%
“…Management of choledocholithiasis in regional settings can often be challenging due to limited access to sub-specialist care, which may limit a health network's ability to provide quick access to specialized procedures. A recent review of 191 consecutive patients [18] who had an ERCP performed by a trained general surgeon in a regional center found that the procedure was completed well above published standards and was cost-effective when comparing overall management costs. Furthermore, despite perceived difficulties surrounding a CBDE, Hodgson et al [19] reported that a caseload of 70 CBDE over 10 years was sufficient in producing an 80% success rate, with only one procedure a year needed to maintain a safe procedure with a 50% success rate.…”
Section: Management Of Choledocholithiasis In a Regional Settingmentioning
confidence: 99%